Home Snack Environments in the United States: Latent Class Analysis Findings From a Home Food Environment Survey. (August 2021) - Hermstad, April; Kegler, Michelle C.; Woodruff, Rebecca C.; Raskind, Ilana G.; Haardörfer, Regine
Snacking occasions have increased in frequency and energy density in recent decades, with considerable implications for diet. Studies have linked presence of foods in the home with intake of those foods. This study examines home snack food inventories among a large sample of U.S. adults using latent class analysis findings to present latent classes of home snack food inventories and multinomial regression to model classes as correlates of percent of calories from fat. Participants ( n = 4, 896) completed an online household food environment survey including presence of 23 snack foods in the home and demographics. Less healthy snack foods were more commonly reported than healthier snack foods ( M = 4.3 vs. M = 3.5). Among White and Latinx participants, high-income households reported greater numbers of both healthier and less healthy snack foods than lower income households, with larger income-based differences in inventory sizes for healthier snack foods. Latent class analysis revealed three classes by inventory size (Small, Medium, and Large) and three classes by inventory content (Healthy Snacks, Standard American, and Limited Standard American). Compared with the Small Inventory class, the Healthy Snacks class had lower caloric intake from fat ( p = .002), the Large and Medium Inventory classes had much higher caloric intake from fat ( p < .0001), and Standard American and Limited Standard American class members had somewhat higher caloric intake from fat ( p < .0001, and p = .0001, respectively). Future research should explore the role of snacks in Americans' diets, their impact on diet quality and health, and how interventions can support healthy home food and snack food environments to foster healthy eating.